2016
DOI: 10.1007/s11695-016-2119-y
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Poor Weight Loss After Laparoscopic Sleeve Gastrectomy: Re-sleeve Vs. Gastric Bypass

Abstract: Following our algorithm, revising an LSG with an LRSG or LRYGB for poor weight loss is feasible with good outcomes. Larger and longer follow-up studies are needed to verify our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(26 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…Another proposed procedure to improve weight loss after a prior SG is the revisional sleeve gastrectomy (Re-SG), which is particularly promising when the original sleeve has dilated. It is found that the overall percentage of excess weight loss following the Re-SG can reach up to 57% at 12 months and up to 60% at 20 months follow-up [ 28 , 29 ]. These percentages seem to exceed weight loss reported for RYGB in the current study; however, contrary to these outcomes Alsabah, S. et al found more weight loss following revisional RYGB than after a Re-SG [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another proposed procedure to improve weight loss after a prior SG is the revisional sleeve gastrectomy (Re-SG), which is particularly promising when the original sleeve has dilated. It is found that the overall percentage of excess weight loss following the Re-SG can reach up to 57% at 12 months and up to 60% at 20 months follow-up [ 28 , 29 ]. These percentages seem to exceed weight loss reported for RYGB in the current study; however, contrary to these outcomes Alsabah, S. et al found more weight loss following revisional RYGB than after a Re-SG [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Revisional surgery was found to be safe . Among 1,300 patients having SG, conversion to RYGB was associated with a mean loss of excess weight of 61.3% after 1 year . Based on retrospective analysis of two cohorts, endoscopic gastrojejunostomy revision also has demonstrated greater effectiveness than medical management for weight regain after RYGB .…”
Section: Executive Summarymentioning
confidence: 99%
“…28 Previous studies have investigated the type of procedure that is best after a SG has failed. 26 In one study with 36 patients, 26 there were no differences in %EWL between re-do SG and conversion to RYGB. Our approach after SG has failed is to perform a RRYGB.…”
Section: Discussionmentioning
confidence: 96%
“…25 Weight regain after bariatric surgery is a major concern for both the patient and the surgeon. 26,27 Research has demonstrated that weight regain is more common after SG (mostly restrictive procedure) than after malabsorptive procedures such as RYGB. 28 Previous studies have investigated the type of procedure that is best after a SG has failed.…”
Section: Discussionmentioning
confidence: 99%